Como ofertar aplicações web Python como um provedor de serviço Shibboleth usando microsserviços - Cardoso, Felipe dos Passos; Andrade, Allex Magno; Mello, Emerson Ribeiro de; Felicissimo, Carolina Howard; Wangham, Michelle Silva (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2020: Companion Proceedings of the 20th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2020.19274, 2020)
The Shibboleth framework provides a module for the Apache HTTP server to deliver SAML assertions to your applications transparently. Python web applications are commonly offered on the Internet through two servers: one application, which implements WSGI, and an HTTP, which acts as a proxy. In the microservice architecture, it is desired that the servers are distributed in such a way that there is only one service running per container. This work presents a form of container composition to offer a Python web application as a Shibboleth Service Provider using the microservices architecture.